Correlation between ionospheric scintillation effects and GNSS positioning over Brazil during the last solar maximum (2012–2014) - Alves, Daniele Barroca Marra [UNESP]; de Souza, Eniuce Menezes; Gouveia, Tayná Aparecida Ferreira [UNESP] (Elsevier, 2019)
GNSS (Global Navigation Satellite Systems) can provide high accuracy positioning at low cost. But, depending on the sources of error, e.g. the atmospheric effects, this accuracy can be degraded. The ionosphere is one of the most important error sources in GNSS positioning. Among several effects caused by the ionosphere, irregularities such as ionospheric scintillations are very relevant. They can cause cycle slips, degrade the positioning accuracy and, when severe enough, can even lead to a complete loss of signal lock. Brazil, in particular, is located in one of the regions most affected by ionospheric scintillations and these effects were intensified during the last solar maximum. The main goal of this paper is to evaluate the impact of scintillation effects on the degradation of positioning during the last solar maximum. Data from 2012 to 2014 of three reference stations located in different regions of Brazil was used. Statistically significant correlations were identified from Spearman's correlation coefficient. Using Odds Ratio, an effect-size statistic, it was possible to see that the chance of large discrepancies in 3D positioning coordinates could be three times greater under strong scintillation effects (S4 ≥ 1) than under moderate ones (0.5<S4<1).
Keywords: GNSS positioning; Ionosphere; Odds ratio; Scintillation; Spearman correlation; Time series